Studi Komparatif Model Problem Based Learning (PBL) dan Model Talking Stick Terhadap Peningkatan Keterampilan Berbicara Siswa SDN Pembina Tolitoli - Rahim, Fitriani Abd; BK, Muh. Khaerul Ummah; Marto, Hasia (LPPM Institut Pendidikan Nusantara Global, 2024)
This study was conducted to identify the differences between classes that implement the Problem Based Learning (PBL) model and classes that implement the Talking Stick model. The purpose of this study was to determine the description of the application of the Problem Based model and the application of the Talking Stick model of students at SDN Pembina Tolitoli, to determine the description of the speaking skills of students at SDN Pembina Tolitoli, to determine whether the Problem Based Learning (PBL) model and the Talking Stick model have a significant effect on improving the speaking skills of students at SDN Pembina Tolitoli, and to determine the differences in comparative results between the Problem Based Learning (PBL) model and the Talking Stick model on improving the speaking skills of students at SDN Pembina Tolitoli. The type of research used in this study is quantitative research using the pre-experimental design method with a one-shot case study design, which was carried out on students at SDN Pembina Tolitoli with a total population of 633 students. The research sample consisted of three classes, namely class VA with 30 students, class VB with 29 students, and class VC with 29 students, which were selected using purposive sampling. Data collection was done through observation and testing, and data analysis using SPSS 25 software. The results of the study showed that the significance value of the Problem Based Learning (PBL) model was 0.212> 0.05 and the Talking Stick model was 0.000 <0.05. Thus, there is a significant influence where, Fcount> Ftable (41.765> 4.88) it can be concluded that Ha is accepted and H0 is rejected which means that the independent variable affects the dependent variable.